Development of common variable immunodeficiency in IgA- and IgG2-deficient patients with systemic lupus erythematosus - Suyama, Kazuhide (Pediatr Nephrol, 2011)
BACKGROUND: There have been few reports on children who developed common variable immunodeficiency (CVID) in association with immunoglobulin A (IgA) and IgG2 deficiencies and systemic lupus erythematosus (SLE). CASE-DIAGNOSIS/TREATMENT: Our patient experienced nephrotic syndrome and acute respiratory distress syndrome (ARDS) caused by influenza A/H1N1 virus infection at 5 years of age. A diagnosis of IgA and IgG2 deficiency and SLE was made on the basis of severe proteinuria, hematuria, hypocomplementemia, high anti-DNA antibody and antinuclear antibody (ANA) titers, and malar rash. However, these clinical signs and symptoms and laboratory features disappeared after the administration of methylprednisolone pulse therapy and prednisolone. For the 5 years following the initial treatment for SLE, the patient experienced a number of infections and had a low serum total IgG level; she was eventually diagnosed with CVID. The administration of intravenous immunoglobulin (IVIG) was required to prevent subsequent infections, and no relapse of SLE was observed. CONCLUSION: We report the development of CVID in an IgA- and IgG2-deficient patient with SLE on the basis of multiple episodes of infection. To prevent the development of CVID in IgA- and IgG2-deficient patients with SLE, it is important to prevent immune dysregulation by the avoidance of infections through the use of IVIG therapy.